Otoliths and Their Applications in Fishery Science - Ferri, Josipa (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on fish otoliths, as one of the most useful and important biological structures for fishery scientists and managers around the world. Collected papers cover several different research areas, from the otolith macro- to the microstructure and microchemistry, analyzing different types of otoliths and investigating various freshwater and marine species in their larval, juvenile and adult stages. Special attention is given to different approaches in otolith research and to many practical applications of such studies. The obtained data served to determine the age and growth of individual fish; to study habitat interactions, migration patterns, or habitats that the fish live in; to detect water temperatures or the presence of certain pollutants in the environment; and to reveal all other vital information about the life history of the fish.